Ø§ÙØ¥ÙØªØ¨ÙØ§Ø³ ÙÙ ÙØºÙÙØ© Ø§ÙÙÙØ±Ø¢Ù ÙØ¯ÙØ±Ù ÙÙ ØªØ¹ÙÙÙÙÙÙÙÙ - Ridha, M. Rasyid (Hunafa: Jurnal Studia Islamika, 2012)
Abstract: The Qurâan is the guidance for all mankind. Therefore, the Arabic language used in the Qurâan should be universal, and be easy to understand by all people. The Qurâan has beautiful, fine and standard ambiguity. Because of the ambiguity of the Qurâan language, almost all the words in the verses of the Qurâan can be interpreted. The ambiguity is one of the semanticsÂ  studies used in studying the meaning. The philosophers and the linguists employ three methods in studying the meaning, namely: 1) explaining the words naturally, 2) describing the sentences naturally, and 3) elaborating the meaning in the process of communication.Â Â  Furthermore, to elaborate the meaning, one should view it from the aspects of word, of sentence, and of what the writer and the speaker need to communicate. All the processesÂ  ofÂ  meaning haveÂ Â  been applied in the Qurâan language in order toÂ  be comprehended by people more easily.Kata Kunci : Ambiguitas, bahasa Arab, Alquran